Comparative Study of Multimodal Therapy in Facial Palsy Patients - Neville, Catriona; Gwynn, Tamsin; Young, Karen; Jordan, Elizabeth; Malhotra, Raman; Nduka, Charles; Kannan, Ruben Yap (Archives of Plastic Surgery, 2022)
Introduction In chronic facial palsy, synkinetic muscle overactivity and shortening causes muscle stiffness resulting in reduced movement and functional activity. This article studies the role of multimodal therapy in improving outcomes.Methods Seventy-five facial palsy patients completed facial rehabilitation before being successfully discharged by the facial therapy team. The cohort was divided into four subgroups depending on the time of initial attendance post-onset. The requirement for facial therapy, chemodenervation, or surgery was assessed with East Grinstead Grade of Stiffness (EGGS). Outcomes were measured using the Facial Grading Scale (FGS), Facial Disability Index, House-Brackmann scores, and the Facial Clinimetric Evaluation scale.Results FGS composite scores significantly improved posttherapy (mean-standard deviation, 60.13 ± 23.24 vs. 79.9 ± 13.01; confidence interval, –24.51 to –14.66, p < 0.0001). Analysis of FGS subsets showed that synkinesis also reduced significantly (p < 0.0001). Increasingly, late clinical presentations were associated with patients requiring longer durations of chemodenervation treatment (p < 0.01), more chemodenervation episodes (p < 0.01), increased doses of botulinum toxin (p < 0.001), and having higher EGGS score (p < 0.001).Conclusions This study shows that multimodal facial rehabilitation in the management of facial palsy is effective, even in patients with chronically neglected synkinesis. In terms of the latency periods between facial palsy onset and treatment initiation, patients presenting later than 2 years were still responsive to multimodal treatment albeit to a lesser extent, which we postulate is due to increasing muscle contracture within their facial muscles.
Keywords: facial paralysis; synkinesis; botulinum toxins-type A; physical therapy modalities; surgery; plastic